ANALISIS RANTAI PASOK SERTA SISTEM ERP DALAM KINERJA OPERASIONAL PT NESTLE INDONESIA - Adeline Oktalia; Emilya; Joicelyn Agriffina; Monica Ella; Fendy Cuandra; Nasar Buntu Laulita (Transpublika Publisher, 2022)
This study will discuss the analysis of ERP implementation at PT Nestle Indonesia. The purpose of implementing the ERP system at PT Nestle is competitive in the increasing global business competition, therefore this system can improve the implementation of the operational performance process to be the most optimal. ERP provides benefits to PT Nestle Indonesia, namely being able to simplify the company's business processes in operating which makes it easier for all divisions to make operational performance more effective and efficient. In addition, PT Nestle Indonesia also implements a supply chain management system so that all stages are made more systematic and structured. By running a supply chain system, it can meet consumer demand, maximize profits, and reduce production costs. This study uses qualitative analysis methods which include collecting, processing, presenting, and describing data. The result of the implementation of the system is the convenience for all divisions to make operational performance more effective and efficient.